Trigonometry

posted by .

Prove that tan (Beta) sin (Beta) + cos (Beta) = sec (Beta)

Please explain.

  • Trigonometry -

    tan*sin + cos
    sin^2/cos + cos^2/cos
    (sin^2+cos^2)/cos
    1/cos
    sec

  • Trigonometry -

    sec (beta) cot(beta)

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. maths

    prove that the length of the perpendicular from the origin to the straight line joining the two points having coordinates ( a cos alpha, a sin alpha) and (a cos beta, a sin beta) is a cos { ( alpha + beta)/2}.
  2. math

    How would you establish this identity: (1+sec(beta))/(sec(beta))=(sin^2(beta))/(1-cos(beta)) on the right, sin^2 = 1-cos^2, that factor to 1-cos * `1+cos, then the denominator makes the entire right side 1+cosB which is 1+1/sec which …
  3. trig

    verify the identity: sec(beta)+ tan (beta)= cos(beta)/ 1-sin(beta)
  4. pre calc

    suppose beta is an angle in the second quadrant and tan beta=-2. Fine the exact vaule of sin beta and cos beta
  5. Trigonometry

    Find the exact value of tan2(Beta) if sin(Beta) = 5/13 (Beta in Quadrant II)
  6. Trigonometry

    Find the exact value of tan2(Beta) if sin(Beta) = 5/13 (Beta in Quadrant II)
  7. physics

    Two radar stations A and B, are separated by horizontal distance of (a=500 metres), they both track the position of a plane C by recording angles (alpha), and (beta) at 1 second intervals. time (sec) 9 10 11 the angle A(alpha) 54.80 …
  8. trig

    evaluate the following in exact form, where the angeles alpha and beta satisfy the conditions: sin alpha=4/5 for pi/2 < alpha < pi tan beta=7/24 for pie < beta < 3pi/2 answer choices A. sin(beta+alpha) B. tan(beta-alpha) …
  9. Trigonometry

    5. Prove: Tan beta sin beta + cos beta = sec beta 6. Prove: ( tan y cos^2 y + sin^2 y)/ (sin y) = cos y+sin y 7. Prove (1+tan theta)/(1-tan theta) = (sec^2+2tan theta) /(1-tan^2 theta)
  10. Trigonometry

    5. Prove: Tan beta sin beta + cos beta = sec beta 6. Prove: ( tan y cos^2 y + sin^2 y)/ (sin y) = cos y+sin y 7. Prove (1+tan theta)/(1-tan theta) = (sec^2+2tan theta) /(1-tan^2 theta)

More Similar Questions